Conceptual of Anti-Gravity Pump - Muhammad Ammar Rifqi Izwan Razif; Hishan, Darwish Rishdan; Muhammad Faris Norzan; Yahaya, Izat (Multidisciplinary Applied Research and Innovation, 2025)
An Anti-Gravity Pump is similar to a hydraulic ram pump which is a method of raising water without the need for an outside energy source. The primary goal is to construct an anti-gravity pump that will lower the complexity and expense of microfluidic systems by raising the water to a height of around 1 meter. Elbow pipes, spring valves, T connectors, pressure gauges, valves, and PVC adhesive are all part of the experimental setup. The objective is to design and develop an anti-gravity pump modelling, as well as to determine and analyze height, pressure and flow rate against time using the anti-gravity pump. The project focuses on modern anti-gravity concepts and technology and uses a PVC-based configuration. The main component of the pump is a pipe that creates a flow route for the water, and a pressure gauge that monitors and analyses liquid pressure in real-time. A valve is an essential component of the pump’s fluid flow control system that enables accurate modifications to the flow conditions. Additionally, spring valves help to regulate flow dynamics and pressure, which enhances experiment accuracy and deepens our comprehension of how various components of the anti-gravity pump system interact. In conclusion, by concentrating on the creation of an affordable and low-maintenance anti-gravity pump, this project seeks to bridge the knowledge gap between theory and practical application in anti-gravity technology.